Fatigue strength prediction of laser powder bed fusion processed Inconel 625 specimens with intentionally-seeded porosity: Feasibility study. (March 2020) - Poulin, J.-R.; Kreitcberg, A.; Terriault, P.; Brailovski, V.
Highlights: Pores smaller than 60 μm do not affect fatigue life of LPBF IN625 in the HCF regime. Seeded porosity strongly reduces the fatigue life of LPBF IN625. El-Haddad's model can predict the fatigue strength of LPBF IN625 with seeded porosity. At 0.3, 0.9 and 2.7% porosity, the fatigue strength of LPBF IN625 is 288, 207 and 170 MPa. Abstract: Inconel 625 fatigue testing specimens with different levels of intentionally-seeded porosity in their gauge section (≤0.1, 0.3, 0.9 and 2.7%) were manufactured by laser powder bed fusion and subjected to stress relief annealing. The morphology, number and distribution of seeded defects were characterized using the micro-computed tomography technique. The effect of the different levels of porosity on the high cycle fatigue behavior of these specimens was studied using room temperature force-controlled fatigue testing according to the ASTM E466 standard (frequency of 30 Hz; R = 0.1) with a runout at 10 7 cycles. The fatigue strength of specimens with the lowest level of porosity (≤0.1%) was found to be 590 MPa. Next, using El-Haddad's formulation of the Kitagawa-Takahashi model defining the limiting conditions for fatigue failure in the presence of defects and Murakami's parameter for defect size rating, the fatigue strengths of specimens with 0.3, 0.9 and 2.7% porosity were predicted at 280, 190 and 160 MPa, respectively. The predicted values were found to deviate by less than 8% from the experimental results, which were, respectively, 288, 207 and 170 MPa.